Discipline, Level, Genre: Integrating Situational Perspectives in a New MD Analysis of University Student Writing. (14th March 2018) - Gardner, Sheena; Nesi, Hilary; Biber, Douglas
Abstract: While there have been many investigations of academic genres, and of the linguistic features of academic discourse, few studies have explored how these interact across a range of university student writing situations. To counter misconceptions that have arisen regarding student writing, this article aims to provide comprehensive linguistic descriptions of a wide range of university assignment genres in relation to multiple situational variables. Our new multidimensional (MD) analysis of the British Academic Written English (BAWE) corpus identifies clusters of linguistic features along four dimensions, onto which academic disciplines, disciplinary groups, levels of study, and genre families are mapped. The dimensions are interpreted through text extracts as: (i) Compressed Procedural Information versus Stance towards the Work of Others; (ii) Personal Stance; (iii) Possible Events versus Completed Events; and (iv) Informational Density. Clusters of linguistic features from the comprehensive set of situational perspectives found across this framework can be selected to inform the teaching of a 'common academic core', and to inform the design of programmes tailored to the needs of specific disciplines.